Investigating unproductive water losses from irrigated agricultural crops in the humid tropics through analyses of stable isotopes of water - Mahindawansha, Amani; Külls, Christoph; Kraft, Philipp; Breuer, Lutz (Copernicus GmbH, 2020)
. Reliable information on water flow dynamics and water losses viairrigation on irrigated agricultural fields is important to improve watermanagement strategies. We investigated the effect of season (wet season and dryseason), irrigation management (flooded and non-flooded), and cropdiversification (wet rice, dry rice, and maize) on soil water flow dynamicsand water losses via evaporation during plant growth. Soil water wasextracted and analysed for the stable isotopes of water (δ2Hand δ18O). The fraction of evaporation losses were determinedusing the Craig–Gordon equation. For dry rice and maize, water in shallowsoil layers (0 to 0.2 m) was more isotopically enriched than in deeper soillayers (below 0.2 m). This effect was less pronounced for wet rice butstill evident for the average values at both soil depths and seasons. Soilwater losses due to evaporation decreased from 40 % at the beginning to25 % towards the end of the dry season. The soil in maize fields showedstronger evaporation enrichment than in rice during that time. A greaterwater loss was encountered during the wet season, with 80 % at thebeginning of the season and 60 % at its end. The isotopic enrichment ofponding surface water due to evaporation was reflected in the shallow soils ofwet rice. It decreased towards the end of both growing seasons during thewet and the dry season. We finally discuss the most relevant soil water flowmechanisms, which we identified in our study to be those of matrix flow,preferential flow through desiccation cracks, and evaporation. Isotope datasupported the fact that unproductive water losses via evaporation can bereduced by introducing dry seasonal crops to the crop rotation system.